Impact of COVID-19 Vaccine and COVID-19 Infection on Vitiligo Activity and Progression - Shi X; Sun Y; Ding X (Dove Medical Press, 2023)
Xiaoyi Shi, Yifang Sun, Xiaolan Ding Department of Dermatology, Peking University People's Hospital, Beijing, People's Republic of ChinaCorrespondence: Xiaolan Ding, Department of Dermatology, Peking University People's Hospital, No. 11 Xizhimen South Street, Xicheng District, Beijing, 100044, People's Republic of China, Tel +8613522658992, Fax +861088325474, Email Lancyding@126.comBackground: Coronavirus disease 2019 (COVID-19) has given rise to several new onset or exacerbated dermatologic disorders including vitiligo. However, the relationship between COVID-19 infection or its associated vaccines and vitiligo progression is unclear.Aim: We investigate the impact of COVID-19 infection and its associated vaccines on vitiligo progression.Methods: A cross-sectional study was performed among patients who visited Department of Dermatology, Peking University People's Hospital between 2022.1 and 2023.6. Detailed information including demographic characteristics, vitiligo clinical features, information on COVID-19 infection and vaccination and disease progression was collected by an electronic questionnaire.Results: Overall, 314 patients with vitiligo completed the questionnaire. 47.5% were males, with an average age of 25.5± 15.9 years. 266 (84.7%) patients had received COVID-19 vaccination, and 70.3% of the patients reported progression of vitiligo after vaccination, mostly within 3 months. 55.6% of the patients had disease progression after the second dose of vaccine. 270 patients experienced COVID-19 infection, and 30.7% of these patients had progression of vitiligo after infection, most of the progression occurred within 1- 2 months. 184 patients (68.2%) interrupted treatment. Analysis results indicated patients in active stage had a higher risk for vitiligo progression after COVID-19 infection and vaccination.Keywords: COVID-19, infection, vaccination, vitiligo, disease progression